Networked Learning in the Real World: Collaboration versus Competition - Sclater, Maddy; Bolander, Klara (Proceedings of the International Conference on Networked Learning, 2002)
This paper examines the application of collaborative learning strategies advocated for online learning and uncovers what, in practical terms, occurred when students undertook an online module forming part of an MSc in Adult and Continuing Education at Glasgow University. The study reveals a tension between the desire to enable an appreciation of the perceived benefits of collaborative learning on one hand, and the competitive, institutional requirement for individualised assessment on the other. This paper illuminates the collaborative and competitive undercurrents of a process that was revealed to be more complex than the simple achievement it was considered at the outset.